Cover Image: Volume 34 Issue 11. Issue 11 (30th October 2019) - Lim, Brian; Forest, Stephen J.; Schultz, Megan L.; Lipsitz, Evan; Michler, Robert E.
Abstract : Front Cover Caption : The cover image is based on the Case Report Aortic Recoarctation and Pseudoaneurysm Five Decades atier Repair by Stephen J. Forest et al., https://doi.org/10.1111/jocs.14201 .